Chemical sensing by band modulation of a black phosphorus/molybdenum diselenide van der Waals hetero-structure. (9th September 2016) - Feng, Zhihong; Chen, Buyun; Qian, Shuangbei; Xu, Linyan; Feng, Liefeng; Yu, Yuanyuan; Zhang, Rui; Chen, Jiancui; Li, Qianqian; Li, Quanning; Sun, Chongling; Zhang, Hao; et al.
Abstract: We report on a new chemical sensor based on black phosphorus/molybdenum diselenide van der Waals hetero-junctions. Due to the atomically thin nature of two-dimensional (2D) materials, surface adsorption of gas molecules can effectively modulate the band alignment at the junction interface, making the device a highly sensitive detector for chemical adsorptions. Compared to sensors made of homogeneous nanomaterials, the hetero-junction demonstrates considerably lower detection limit and higher sensitivity toward nitrogen dioxide. Kelvin probe force microscopy and finite element simulations have provided experimental and theoretical explanations for the enhanced performance, proving that chemical adsorption can induce significant changes in band alignment and carrier transport behaviors. The study demonstrates the potential of van der Waals hetero-junction as a new platform for sensing applications, and provides more insights into the interaction between gaseous molecules and 2D hetero-structures.